Fatigue tests and design of diamond bird-beak SHS T-joints under axial loading in brace. (March 2016) - Tong, Lewei; Xu, Guowen; Yan, Dongqiang; Zhao, Xiao-Ling
Abstract: A diamond bird-beak square hollow section (SHS) T-joint is different from a conventional SHS T-joint as the brace and chord members both rotate 45°. This paper deals with fatigue behavior of such joints through fatigue tests and proposed fatigue design curves ( S r, hs – N curves). Diamond bird-beak SHS T-joints (DBB T-joints) with a unique set of geometric non-dimensional key parameters ( β, 2 γ and τ ) were used for fatigue tests. Cracking patterns were observed during the fatigue tests. Based on the fatigue data and stress concentration factors (SCFs) derived by the authors of this paper, new fatigue design curves ( S r, hs – N curves) using hot spot stress concept were discussed by means of deterministic method and least-square method, respectively. Finally, fatigue strength was compared between DBB T-joints and conventional SHS T-joints. The results indicated that DBB T-joints have better fatigue behavior when β is not greater than 0.7. Highlights: Performed fatigue tests on diamond bird-beak square hollow section (SHS) T-joints Proposed fatigue design rule for diamond bird-beak square hollow section T-joints Diamond bird-beak SHS T-joints have longer fatigue life than conventional T-joints.